Spatial extent and temporal variability of Greenland firn aquifers detected by ground and airborne radars. Issue 12 (20th December 2016) - Miège, Clément; Forster, Richard R.; Brucker, Ludovic; Koenig, Lora S.; Solomon, D. Kip; Paden, John D.; Box, Jason E.; Burgess, Evan W.; Miller, Julie Z.; McNerney, Laura; Brautigam, Noah; Fausto, Robert S.; et al.
Abstract: We document the existence of widespread firn aquifers in an elevation range of ~1200–2000 m, in the high snow‐accumulation regions of the Greenland ice sheet. We use NASA Operation IceBridge accumulation radar data from five campaigns (2010–2014) to estimate a firn‐aquifer total extent of 21, 900 km 2 . We investigate two locations in Southeast Greenland, where repeated radar profiles allow mapping of aquifer‐extent and water table variations. In the upper part of Helheim Glacier the water table rises in spring following above‐average summer melt, showing the direct firn‐aquifer response to surface meltwater production changes. After spring 2012, a drainage of the firn‐aquifer lower margin (5 km) is inferred from both 750 MHz accumulation radar and 195 MHz multicoherent radar depth sounder data. For 2011–2014, we use a ground‐penetrating radar profile located at our Ridgeline field site and find a spatially stable aquifer with a water table fluctuating less than 2.5 m vertically. When combining radar data with surface topography, we find that the upper elevation edge of firn aquifers is located directly downstream of locally high surface slopes. Using a steady state 2‐D groundwater flow model, water is simulated to flow laterally in an unconfined aquifer, topographically driven by ice sheet surface undulations until the water encounters crevasses. Simulations suggest that local flow cells form within the Helheim aquifer, allowing water to discharge in the firn at the steep‐to‐flat transitions of surface topography. Supported by visible imagery, we infer that water drains into crevasses, but its volume and rate remain unconstrained. Key Points: Firn aquifers represent a total area of 21, 900 km 2 when inferred from airborne radar data collected between 2010 and 2014 Water table interannual variations imply filling and drainage Water flows in the firn aquifer under low hydraulic gradients following local surface topography